2017
DOI: 10.1371/journal.pone.0185561
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for serum insulin-like growth factor I (IGF-I) in healthy Chinese adults

Abstract: PurposeTo determine serum insulin-like growth factor 1 (IGF-I) levels in healthy Chinese adults, establish reference ranges for serum IGF-I levels and observe the effects of age, sex, body mass index (BMI) and geographical region on serum IGF-I levels.MethodsIn total, 2791 healthy adults (1339 males and 1452 females) from the north (Beijing) and south (Guizhou Province) of China were recruited following a questionnaire survey, physical examination and laboratory examination. Both sexes were divided into 13 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
(49 reference statements)
8
40
0
Order By: Relevance
“…ER was defined as a random GH<1.0 ng/ml or a GH nadir<0.4 and age-gender normalized IGF-1 (27). The IGF-1 reference range used in this study referred to our published article (28). Repeated surgery, octreotide LAR treatment and observation were recommended for recurrent patients according to the radiological findings and hormone levels.…”
Section: Study Design and Follow-upmentioning
confidence: 99%
“…ER was defined as a random GH<1.0 ng/ml or a GH nadir<0.4 and age-gender normalized IGF-1 (27). The IGF-1 reference range used in this study referred to our published article (28). Repeated surgery, octreotide LAR treatment and observation were recommended for recurrent patients according to the radiological findings and hormone levels.…”
Section: Study Design and Follow-upmentioning
confidence: 99%
“… 9 , 19 - 21 IGF1 concentration decreased with increasing age, with no obvious additional decline after approximately 50 years of age. 22 24 Thus, it has been speculated that the inverse association between IGF1 and age might be the key determinant of the varied association patterns by menopausal status. 9 Age at menarche is an indicator of puberty development and has also been associated with higher concentrations of IGF1.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for this difference is the use of different assay kits in the measurement of serum IGF-1 levels between the two studies. Previous studies have reported significant differences in serum IGF-1 levels when using different assay kits, even though the samples were from the same population [28][29][30] . Different assay kits have different age-and sex-specific reference ranges, and this might affect the upper and lower limit of each study's serum IGF-1 levels.…”
Section: Discussionmentioning
confidence: 99%